Marzamemi Does Not Exist. The Invention of a Place between New Sicilianisms and Contemporary Aesthetics of the Picturesque - Mazzucchelli, Francesco (E|C, 2022)
Marzamemi is a beautiful coastal village located in South-Eastem Sicily. Until the end of last century, it has been a touristic destination for a limited and mainly local tourism. In the last decades, the flow of tourists has dramatically increased, transforming this small fishermen's village into one of the most popular Sicilian destinations. Marzamemi - and especially its piazza, that of this village is often a figurative synecdoche, in its various representations circulating in media and social media - has thus become, in a short time, a "symbol of Sicilianity", able to condense a certain idea of Sicily, through a panoply of stereotypical motifs and figures, reproducing a form of "sicilianism". The contemporary visual identity of Marzamemi resonates with a contemporary aesthetics of the 'picturesque', what is today called as "instagrammability". The article reflects on the strategies through which the visual identity of Marzamemi stages a sort of scenario that aims at self-proposing as a cohesive system of "instagrammable sites", that re-articulates new syntaxes for the tourists' forms of life. This reflection moves both from a direct observation of places and practices, and from the analysis of a corpus of social posts (especially on lnstagram), with the aim of tracing some of the discursive strategies of invention and re-invention of this place.